Harry Potter and the goblet of fire - Newell, Mike, 1942-; Kloves, Steven; Heyman, David, 1961-; Radcliffe, Daniel, 1989-; Watson, Emma, 1990-; Grint, Rupert, 1988-; Gambon, Michael; Gleeson, Brendan; Isaacs, Jason, 1963-; Rickman, Alan.; Spall, Timothy, 1957-; Smith, Maggie, 1934-; et al. ([Burbank, Calif.] : Warner Home Video, 2005)
Harry's fourth year at Hogwarts is marked by the Quidditch World Cup and the Triwizard Tournament, in which student representatives from three different wizarding schools compete in a series of increasingly challenging contests.
Based on the novel by J.K. Rowling.
Originally released as a motion picture in 2005.
Director of photography, Roger Pratt ; art directors, Mark Bartholomew ... [et al.] ; editor, Mick Audsley ; music, Patrick Doyle ; costume designer, Jany Temime ; production designer, Stuart Craig ; visual effects supervisors, Tim Burke, Charley Henley, Jim Mitchell, Stuart Pitcher ; special effects supervisor, Dominic Tuohy.
Daniel Radcliffe, Emma Watson, Rupert Grint, Robbie Coltrane, Michael Gambon, Brendan Gleeson, Maggie Smith, Gary Oldman, Miranda Richardson, Ralph Fiennes, Alan Rickman, Jason Isaacs, Timothy Spall.
MPAA rating: PG-13; for sequences of fantasy violence and frightening images.
DVD; Dolby digital 5.1; NTSC, region 1; dual layer; widescreen.
Keywords: Potter, Harry -- (Fictitious character) -- Drama; Wizards -- England -- Drama; Magic -- England -- Drama; Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Drama; Schools -- England -- Drama; Contests -- Drama; Feature films; Films for the hearing impaired